Perancangan Aplikasi Pengelolaan Keuangan dengan Menggunakan Android Studio - Salshavira, Najwabilla (Journal of Informatics and Advanced Computing (JIAC), 2024)
Financial management is an important aspect of everyday life, but it is often challenging for many individuals and families. This article discusses the development of an Android-based financial management application using Android Studio, which aims to improve financial literacy and financial management efficiency. This application offers transaction recording, report generation, bill reminders, and visual analysis features to facilitate understanding of financial patterns. By utilizing modern technology, this application is expected to help users make better financial decisions and improve the financial well-being of the community. The development of this application uses the use case and class diagram design methods to ensure optimal system design.